2007
DOI: 10.5194/acp-7-1585-2007
|View full text |Cite
|
Sign up to set email alerts
|

The T1-T2 study: evolution of aerosol properties downwind of Mexico City

Abstract: Abstract. As part of a major atmospheric chemistry and aerosol field program carried out in March 2006, a study was conducted in the area to the north and northeast of Mexico City to investigate the evolution of aerosols and their associated optical properties in the first few hours after their emission. The focus of the T1-T2 aerosol study was to investigate changes in the specific absorption α ABS (absorption per unit mass, with unit of m 2 g −1 ) of black carbon as it aged and became coated with compounds s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 42 publications
(48 reference statements)
11
73
1
Order By: Relevance
“…Enhanced mixing and removal processes likely contributed to the observed decrease in background concentrations of organic carbon at T1 (Doran et al, 2007) after the strongest cold front passed over the region on 23 March. Marley et al (2009a) found that aerosol scattering decreased when rain was observed between 23 and 27 March since scattering aerosols are partially inorganic and hydrophilic and expected to be scavenged more readily.…”
Section: Synoptic Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Enhanced mixing and removal processes likely contributed to the observed decrease in background concentrations of organic carbon at T1 (Doran et al, 2007) after the strongest cold front passed over the region on 23 March. Marley et al (2009a) found that aerosol scattering decreased when rain was observed between 23 and 27 March since scattering aerosols are partially inorganic and hydrophilic and expected to be scavenged more readily.…”
Section: Synoptic Conditionsmentioning
confidence: 99%
“…As described by Doran et al (2007), radar wind profilers at each site obtained wind speed and direction profiles up to 4 km above ground level (a.g.l.). A radar wind profiler was also deployed at Veracruz, located on the Gulf of Mexico east of Mexico City to obtain wind information aloft farther downwind of Mexico City.…”
Section: Observational Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…These properties are not static in time; instead, evolving as particles, they are transported through the atmosphere as a result D. B. Atkinson et al: Using spectral methods to obtain particle size information of chemical processing, scavenging and changes in the environmental conditions (e.g., relative humidity and temperature) (Doran et al, 2007;George and Abbatt, 2010;Lack and Cappa, 2010).…”
Section: Introductionmentioning
confidence: 99%